AUTOMATED APPROACH FOR COLOR IMAGE GENERATION (Journal of Engineering, 2008)
We introduce a general technique for “generating” images by automatic transferring luminance and color between a source and a target images both can be in black/ white, grayscale and color images at any time. Although the general problem of adding luminance and chromatic values to a target image was not exact, so, the current approach attempts to provide a method to help minimize the a mount of human labor required for this task. This method perform the image generating rely on luminance matching techniques between the source and target pixel neighborhood, and transfer the best pixels of neighborhood matching, i.e., luminance and chromatic information from source to target. The results demonstrate this technique introduce natural-looking generating in entertaining manner and work surprisingly well for a large variety of images, no more time of frustration attempting to get just the look you want without human intervention. It is compatible with such popular image processing software as “A dobe PhotoShop”. Although this study find a new method focus only on the homogeneous images, future work will solve the problems of non-homogeneous images.